Blockchain-Driven Supply Chain Innovation for the FMCG Sector - Chaudhary, Sumip; Tamang, Ramesh; G.M., Ashok (Journal of Himalaya College of Engineering, 2025)
Despite Nepal’s cryptocurrency ban, blockchain technology has considerable potential for improving transparency, security, and traceability in the country’s supply chain systems. This study demonstrates the viability of applying a blockchain-based framework in the Fast-Moving Consumer Goods (FMCG) industry to increase product authenticity and prevent counterfeiting. By giving unique digital identifiers to products, the technology enables verification at each level of the supply chain via an immutable decentralized ledger. Implemented and tested on the Ethereum Sepolia testnet, the prototype achieved 96% traceability accuracy and decreased transaction latency to 7 seconds, demonstrating blockchain’s practical usability within Nepal’s legislative limits. The findings confirm that blockchain may run securely and efficiently without relying on cryptocurrencies, providing a foundation for future study, infrastructure development, and regulatory adaption.